Keanekaragaman dan dominansi superclass pisces di pesisir Kabupaten Pasuruan sebagai bahan ajar pada materi keanekaragaman hayati kelas x - Wanandi, Ichsan Bakhtiar; Nugroho, Endik Deni (Undiksha, 2023)
Indonesia is an archipelagic country with the highest level of biodiversity after Brazil. The diversity of Superclass Pisces (fish) in Indonesia is very significant. Indonesia's coastal resources are the centre of the richest tropical marine biodiversity in the world, where 90% of the fish catch comes from coastal waters within a 12 nautical mile radius of the coastline. From the data obtained, seafood from the coast of Pasuruan Regency is relatively abundant. In Kalirejo Village, Kraton District, most residents work as fishermen. Fishermen in Kalirejo Village usually look for fish on the coast of Pasuruan Regency. The fish obtained were dominated by ilat-ilatan fish (tongue fish). In the southern part of the coast of Pasuruan Regency, to be precise, from the Kalirejo Village area, Kraton District, there has been no research on the diversity and dominance of Superclass Pisces in the Madura Strait waters as well as a local potential that can be used as teaching materials. Local potential can be associated with learning, especially in learning Biology as a learning resource. Utilization of the local potential of the Superclass Pisces in the Madura Strait Waters can potentially become teaching material in biology lessons in high schools, especially in the CP (Learning Outcomes) of the Diversity of Living Things and Their Role in the subject of Diversity with the scope of the Spread of Fauna in Indonesia. Therefore, researchers are interested in conducting a research entitled